Breakdown of the Gutenberg‐Richter relation for microearthquakes induced by hydraulic fracturing: influence of stratabound fractures. (23rd May 2014) - Eaton, David W.; Davidsen, Jörn; Pedersen, Per Kent; Boroumand, Neda
ABSTRACT Hydraulic fracturing, a powerful completion technique used to enhance oil or gas production from impermeable strata, may trigger unintended earthquake activity. The primary basis for assessment of triggered and natural seismic hazard is the classic Gutenberg‐Richter (G‐R) relation, which expresses scale‐independent behaviour of earthquake magnitudes. Here we use a stochastic approach to simulate and test magnitude‐distance trends expressed by microseismic catalogues derived from three hydraulic fracture monitoring programmes in North America. We show that a widely observed rapid fall‐off in large‐magnitude events, almost universally quantified using the G‐R b value, may in our case be an artefact of the strongly laminated character of the stimulated oil and gas reservoirs. We also show that, for the three reservoirs considered, mechanical bed thickness can be approximated by a lognormal distribution. For a stratabound fracture network, this leads asymptotically to a Gaussian decay for induced magnitudes. We show that the stratabound model provides a more significant correspondence with our observations. If applicable in general, this result has important implications for determining the energy balance of hydraulic fracture systems (i.e. radiated seismic energy versus injected energy) as well as hazard assessments based on the probability of occurrence of anomalous seismic events.